2022
DOI: 10.1021/jacs.2c05687
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light Photocatalyzed peri-(3 + 2) Cycloadditions of Quinolines

Abstract: Cycloaddition reactionsepitomized by the Diels–Alder reactionoffer an arguably unmatched springboard for achieving chemical complexity, often with excellent selectivity, in a modular single step. We report the synthesis of aza-acenaphthenes in a single step by an unprecedented formal peri-(3 + 2) cycloaddition of simple quinolines with alkynes. A commercially available iridium complex exerts a dual role of photosensitizer and photoredox catalyst, fostering a cyclization/rearomatization cascade. The initial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…Screening various photocatalysts to identify properties required to initiate the chain reaction revealed that only photocatalysts that are both triplet sensitizers with an E T of ∼60 kcal/mol and highly oxidizing were successful ( Ir-F and 4CzIPN; see the Supporting Information). In order to probe whether a biphotonic pathway could possibly initiate the chain reaction, the initial kinetics were recorded in dependency on the irradiation intensity . It was found that the initial reaction rate increases with the excitation power P (for λ max = 450 nm: product yield ∝ P 0.85 ; for λ max = 415 nm: product yield ∝ P 1.0 ).…”
Section: Resultsmentioning
confidence: 99%
“…Screening various photocatalysts to identify properties required to initiate the chain reaction revealed that only photocatalysts that are both triplet sensitizers with an E T of ∼60 kcal/mol and highly oxidizing were successful ( Ir-F and 4CzIPN; see the Supporting Information). In order to probe whether a biphotonic pathway could possibly initiate the chain reaction, the initial kinetics were recorded in dependency on the irradiation intensity . It was found that the initial reaction rate increases with the excitation power P (for λ max = 450 nm: product yield ∝ P 0.85 ; for λ max = 415 nm: product yield ∝ P 1.0 ).…”
Section: Resultsmentioning
confidence: 99%
“…This reaction displays good selectivity toward the formation of one isomer and affords valuable functionalized aromatic heterocycles that have been established as privileged motifs in pharmaceutically active compounds . Additional studies revealed a novel photochemical cascade with certain substitution patterns . In this study, we greatly expand upon the substrate scope to more challenging examples such as disubstituted alkenes and allenes under Lewis acid-mediated conditions developed in the Brown lab (Scheme C).…”
Section: Introductionmentioning
confidence: 99%
“…Besides 5substituted quinolines, other substitution patterns (38−53) were also found to be compatible in this reduction. Bromo (39,43), primary benzylic alcohol (40,50), ester (41,44), cyano (42), methyl ether (45), chloro (47,52), and boron pinacol ester ( 49) were all tolerated. Similarly, isoquinolines (54−56) were smoothly reduced under the standard conditions.…”
mentioning
confidence: 99%
“…Our dearomatization exploration commenced with the hypothesis that the photoexcited quinolinium intermediate might be reduced by a hydride reductant, such as silane reagents, to enable direct addition and reduction of the heteroarenes. During the solvent investigation, formation of an intriguing hydrosilylated product 11 was observed and subsequently optimized (Table , entry 1) .…”
mentioning
confidence: 99%
See 1 more Smart Citation